1996
DOI: 10.1128/aem.62.8.2839-2844.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cross-resistance of the diamondback moth indicates altered interactions with domain II of Bacillus thuringiensis toxins

Abstract: We compared responses to six insecticidal crystal proteins from Bacillus thuringiensis by a Cry1A-resistant strain (NO-QA) and a susceptible strain (LAB-P) of the diamondback moth, Plutella xylostella. The resistant strain showed >100-fold cross-resistance to Cry1J and to H04, a hybrid with domains I and II of Cry1Ab and domain III of Cry1C. Cross-resistance was sixfold to Cry1Bb and threefold to Cry1D. The potency of Cry1I did not differ significantly between the resistant and susceptible strains. Cry2B did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 45 publications
3
32
0
2
Order By: Relevance
“…We first confirmed the susceptibility of the DBM strain 'Fuzhou' to three Lepidoptera-specific Bt toxins, Cry1Ac, Cry1Ab, and Cry1Bd by determining the concentration of the toxin that was lethal to 50% of the DBM (LC50). The LC50s of Cry1Ac, Cry1Ab, and Cry1Bd against the third larvae of this strain were 4.35 mg/L, 0.49 mg/L, and 0.05 mg/L, respectively, indicating that the Fuzhou strain is highly susceptible to Cry1Ac, Cry1Ab, and Cry1Bd, as reported previously [13,[25][26][27][28][29].…”
Section: Binding Spectrum Of Bt Toxinssupporting
confidence: 86%
See 2 more Smart Citations
“…We first confirmed the susceptibility of the DBM strain 'Fuzhou' to three Lepidoptera-specific Bt toxins, Cry1Ac, Cry1Ab, and Cry1Bd by determining the concentration of the toxin that was lethal to 50% of the DBM (LC50). The LC50s of Cry1Ac, Cry1Ab, and Cry1Bd against the third larvae of this strain were 4.35 mg/L, 0.49 mg/L, and 0.05 mg/L, respectively, indicating that the Fuzhou strain is highly susceptible to Cry1Ac, Cry1Ab, and Cry1Bd, as reported previously [13,[25][26][27][28][29].…”
Section: Binding Spectrum Of Bt Toxinssupporting
confidence: 86%
“…Some proteins also bound specifically to the Cry1Ac and Cry1Ab toxins, and each toxin captured several proteins in particular ( Figure 1, Supplemental Closer attention was paid to the proteins captured by Cry1Bd. This Cry toxin has the greatest potential to be used against DBM because the field population of this insect has evolved cross-resistance to four Bt toxins including Cry1Ac and Cry1Ab, but remains highly susceptible to Cry1Bd [13,25,[27][28][29]35]. Therefore, if Cry1Bd is to be used to control this pest, it is important to investigate potential Cry1Bd receptors [36,37].…”
Section: Supplemental Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabashnik et al (1996) reported resistance to Cry1Ba had low or no levels of cross-resistance to other crystal proteins, such as Cry1Aa, Cry1Ab, Cry1Ac, Cry1Fa, Cry1Ja. Cry1A-resistant strain (NO-QA) of the diamondback moth showed high levels of resistance to Cry1Aa, Cry1Ab and Cry1Ac and low or no levels of cross-resistance to Cry1Ba (Tabashnik et al 1996). Rang et al (2004) reported that Cry1Ab and Cry1Ac in Spodoptera frugiperda, competed for the same binding site, whereas Cry1Ba and Cry1Ca competed for different binding sites.…”
Section: Discussionmentioning
confidence: 98%
“…Among them, resistance of the cereal stem borer, Busseola fusca, in South Africa and fall armyworm, Spodoptera frugiperda, in Puerto Rico, to Bt corn producing either Cry1Ab (Kruger et al 2009) or Cry1F (Matten et al 2008), respectively, were studied. Also studied were the pink bollworm pest, Pectinophora gossypiella, in India (Bagla 2010), cotton bollworm, Helicoverpa zea, in the USA (Luttrell et al 2004;Tabashnik et al 2008Tabashnik et al , 2009) and diamondback moth, Plutella xylostella, in the USA (Tabashnik et al 1996;Cao et al 1999). Liu et al (2000) studied binding, toxicity and cross-resistance of Bt Cry1C in diamondback moth and bollworm, Helicoverpa punctigera, in Australia (Downes et al 2010) on development of resistance to Bt cotton producing Cry1Ac and Cry2Ab.…”
Section: Introductionmentioning
confidence: 99%